Tatalaksana Menyeluruh Wanita Usia 60 Tahun dengan Hipertensi Derajat 1 dan Skabies Melalui Kedokteran Keluarga - Agung, Lovina Ramadhita; Saftarina, Fitria (Medula, 2024)
Family doctors provide evidence-based medicine services with a patient-centered and family-focused approach to identify clinical problems, risk factors, and patient management. This article is compiled using a case report method according to research needs. The data used are primary data obtained through anamnesis, both auto and alloanamnesis, physical examination, home visits to obtain data related to family, psychosocial and environment. A holistic diagnosis of various factors is carried out from beginning to end to solve the problem holistically. A 60-year-old woman was diagnosed with Grade I Hypertension and Scabies. The patient has internal risk aspects, namely obesity, poor hygiene, unbalanced diet, low knowledge of the disease, and stress. The external risk in this case is the lack of family knowledge regarding the patient's disease. Then, comprehensive management is carried out for the patient and family. Through this approach, it is expected to be able to improve the patient's knowledge, perspective, and actions. The role of the family to change the patient's lifestyle to be healthier as support for the patient, such as reminding to take medication and inviting exercise greatly affects the results of holistic management. The complexity of this problem requires time and cooperation between family doctors, patients, and families.